The unfinished history of the Iran-Iraq War faith, firepower, and Iran's Revolutionary Guards - Samuel, Annie Tracy ca. 20./21. Jh (Cambridge University Press, 2022)
The Islamic Revolutionary Guard Corps (IRGC), founded after the Iranian revolution in 1979, is one of the most powerful and prominent but least understood organizations in Iran. In this book, Annie Tracy Samuel presents an innovative and compelling history of this organization and, by using the Iran-Iraq War as a focal point, analyzes the links between war and revolution. Tracy Samuel provides an internal view of the IRGC by examining how the Revolutionary Guards have recorded and assessed the history of the war in the massive volume of Persian language publications produced by the organization's top members and units. This not only enhances our comprehension of the IRGC's roles and power in contemporary Iran, but also demonstrates how the history of the Iran-Iraq War has immense bearing on the Islamic Republic's present and future. In doing so, the book reveals how analyzing Iran's history provides the critical tools for understanding its actions today